Creating Nations - T. Espák, Gabriella (Hungarian Journal of English and American Studies, 2021)
Book review: Mann, Jatinder. The Search for a New National Identity: The Rise of Multiculturalism in Canada and Australia, 1890s-1970s. Interdisciplinary Studies in Diasporas 2. New York: Peter Lang, 2016. 339 pages. ISBN 9781433133695. Hb. 88.24.